2020
DOI: 10.1136/gutjnl-2020-322118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mortality risk in patients with cirrhosis and COVID-19 compared with patients with cirrhosis alone and COVID-19 alone: multicentre matched cohort

Abstract: ObjectiveComorbid conditions are associated with poor prognosis in COVID-19. Registry data show that patients with cirrhosis may be at high risk. However, outcome comparisons among patients with cirrhosis+COVID-19 versus patients with COVID-19 alone and cirrhosis alone are lacking. The aim of this study was to perform these comparisons.DesignA multicentre study of inpatients with cirrhosis+COVID-19 compared with age/gender-matched patients with COVID-19 alone and cirrhosis alone was performed. COVID-19 and cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
240
1
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(276 citation statements)
references
References 20 publications
18
240
1
17
Order By: Relevance
“…The presence of acute-on-chronic liver failure (ACLF) was also similar in the 2 cirrhosis groups (29.7% vs. 22.8%) as was mortality in patients with ACLF (55% vs. 36%; p = 0.25) although the number of cases was small. 27 Taken together, we cannot currently conclude that COVID-19 increases the risk of ACLF or mortality in patients with cirrhosis more than other causes of decompensation. However, in patients with COVID-19, mortality is markedly greater in those with cirrhosis than in those without cirrhosis.…”
Section: Cirrhosismentioning
confidence: 85%
“…The presence of acute-on-chronic liver failure (ACLF) was also similar in the 2 cirrhosis groups (29.7% vs. 22.8%) as was mortality in patients with ACLF (55% vs. 36%; p = 0.25) although the number of cases was small. 27 Taken together, we cannot currently conclude that COVID-19 increases the risk of ACLF or mortality in patients with cirrhosis more than other causes of decompensation. However, in patients with COVID-19, mortality is markedly greater in those with cirrhosis than in those without cirrhosis.…”
Section: Cirrhosismentioning
confidence: 85%
“…With the paucity of data, it remains unclear whether such liver injury observed in COVID-19 as well as SARS and MERS infection were inflammation-mediated or from direct viral infection. A recent multi-centre North American matched cohort study showed that cirrhotic patients with COVID-19 had similar mortality to cirrhotic patients alone, and Charlson Comorbidity Index was the only independent predictor for mortality [ 42 ].…”
Section: Narrative Reviewmentioning
confidence: 99%
“…1 2 Although both studies reported an increased risk of mortality following SARS-CoV-2 infection in cirrhotics, as recently confirmed by other studies in both cirrhotic and liver transplanted patients, they differ for some aspects. [1][2][3][4] Bajaj and colleagues enrolled younger patients (61.0±10.6 vs 67.6±10.1 years old), mostly women (73% vs 30%), and they found similar survival in cirrhotic patients with and without COVID-19, in contrast with what we previously reported. 1 2 In the North American cohort, the Charlson Comorbidity Index (CCI) was independently associated with mortality (OR 1.23, 95% CI 1.11 to 1.37, p<0.0001), 1 while in our cohort CLIF-OF (OR 1.77, 95% CI 1.24 to 2.54, p=0.002) and moderate to severe lung failure (OR 1.86, 95% 1.00-3.44, p=0.048) independently predicted mortality according to a logistic regression model.…”
Section: Combination Of Clif-of and CCI Predicts Survival In Patientsmentioning
confidence: 50%
“…[1][2][3][4] Bajaj and colleagues enrolled younger patients (61.0±10.6 vs 67.6±10.1 years old), mostly women (73% vs 30%), and they found similar survival in cirrhotic patients with and without COVID-19, in contrast with what we previously reported. 1 2 In the North American cohort, the Charlson Comorbidity Index (CCI) was independently associated with mortality (OR 1.23, 95% CI 1.11 to 1.37, p<0.0001), 1 while in our cohort CLIF-OF (OR 1.77, 95% CI 1.24 to 2.54, p=0.002) and moderate to severe lung failure (OR 1.86, 95% 1.00-3.44, p=0.048) independently predicted mortality according to a logistic regression model. 5 In the present study, acute-on-chronic liver failure was defined according to the North American Consortium for the Study of End-Stage Liver Disease (NACSELD) criteria, while we referred to the CLIF consortium definition and score.…”
Section: Combination Of Clif-of and CCI Predicts Survival In Patientsmentioning
confidence: 50%